Le verre de Sabra al-Mansuriya : (Kairouan, Tunisie) milieu Xe-milieu XIe siècle : production et consommation : vaisselle - contenants - vitrages - Foy, Danièle, (Archaeology of the Maghreb ;, 2020)
Knowledge of Islamic glass and its craftsmanship in the medieval period has relied heavily on Middle Eastern literature. The study of workshop and rich glass assemblage from Sabra al-Mansuriya (Kairouan), the Fatimid capital founded in 947/948 and destroyed in 1057, shows that Ifriqiya followed the technological evolutions of glass craftsmanship.